Visual Attention Analysis of Perspective Images Using the Eye Tracking Method - Purba, Andres Taruli; Br Purba, Laura Natalia; Haliza, Della; Siagian , Hendricus; Simanjuntak, Pransisko Oktavianus; Evta Indra (Fakultas Teknologi dan Ilmu Komputer Universitas Prima Indonesia, 2024)
In this research, eye tracking was applied to observe students' visual attention to three perspective images, each of which has a Region of Interest (RoI). In initial research, it was found that the majority of students faced difficulties in concentrating during the learning process. The aim of this research is to analyze the visual attention of perspective drawings in adolescents in an effort to increase learning concentration. Eye tracking was used as a research instrument to monitor the eye movements of 70 students objectively and in real-time who were guided by giving assignments to look for certain objects. This study showed that in terms of perception speed and focus duration, female participants outperformed male participants. However, overall the level of concentration of teenagers cannot be said to be good. These findings provide important knowledge for educators in creating more effective visual content to improve student concentration and understanding.